Preparation of Flame Resistant Retanning Product for Glove Leather - Zehra, Beena; Solangi, Barkat Ali; Nadeem, Uzma (Indonesian Scholar Society, 2022)
Leather gloves are very light leather used for protection against various risks. A flame-resistant product is needed to increase the flame resistance of natural leather. In this study, 02 flame resistant retanning products had been prepared utilizing waste leather protein extract with phosphoric acid and formaldehyde. These products had been applied at the retanning stage during leather processing. The utilization of phosphorus compounds chemically reacted with or deposited in leather fibers represented the most significant contribution in durable flame retardancy. The final prepared leathers had been characterized for different physical properties such as radiation and electric heat resistance, flame spread resistance and impact of spatter. These products had been found to be compatible with commercial flame-resistant products. The thermal behavior of prepared leathers showed significant resistance.